Evaluation of Closed System Transfer Devices in Preventing Chemotherapy Agents Contamination During Compounding Process—A Single and Comparative Study in China - Tang, YiWen; Che, XiaoTian; Wang, Yao Lei; Ye, Xin; Cao, Wan Li; Wang, Yi (Frontiers in Public Health, 2022)
We performed a comparative study to investigate the efficacy of closed system transfer devices (CSTD) on safe handling of injectable hazardous drugs. Methods: The exposure assessments of cyclophosphamide and cytarabine were performed under traditional or CSTD device. For preparation related activity, contamination samples included the environment of chemotherapy agent were handled and the use of protective equipment (such as gloves and masks) were collected. The contamination analysis was performed by LC-MS/MS. A 6-item form was distributed monthly (form M1-M6, total 6 months) to assess the pharmacists’ experience on ergonomics, encumbrance, safety impression and to establish a direct comparison. Results: Totally, 96 wiping samples were collected throughout the study. the percentages of contaminated cyclophosphamide samples under CSTD were -37.8%, -41.6%, -67.7%, -47.3%, -22.9% and cytarabine with -12.3%, -12.1%, -20.6%, -69.6%, -56.7% for left countertop, right countertop, medial glass, air-intake vent and door handle, respectively with the traditional devices. The trends were similar for pharmacist devices: -48.2% and -50.0% for masks and gloves cyclophosphamide contamination, -18.0% and -42.4% for cytarabine, respectively. Similarly, cyclophosphamide contamination percentage was found with -16.6%, -6.0% and -22.3% for dispensing table, transfer container and dispensing basket under CSTD condition, respectively. Likewise, the percentages of contaminated cytarabine samples were -28.5%, -22.5% and -46.2%, respectively with the traditional devices. A high level of satisfaction was consistently associated with ergonomics for CSTD during compounding process. Meanwhile, a slightly decreased satisfaction on ergonomics, encumbrance and safety impression was observed for traditional system between M2 and M3. Conclusion: The proper use of a CSTD may significantly decrease contamination by these drugs and consequently decrease exposure risk on isolator surfaces and pharmacist devices as compared to traditional compounding devices.